2005
DOI: 10.1890/05-0431
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Weather and Disease as Causes of Decline in Two Populations of Boreal Toads

Abstract: Abstract. Two populations of boreal toads (Bt{/o boreas) experienced drastic declines in abundance in the late 1990s. Evidence supported the hypothesis of disease (the chytrid fungus. Batrachochytrium dendrobatidis) as the cause of these declines. but other hypotheses had not been evaluated. We used an II-year capture-recapture data set to evaluate weather and disease as causes of these declines. We developed sets of mathematical models that reflected hypothesized relationships between several weather variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 30 publications
1
57
1
Order By: Relevance
“…The initial decline observed for the corroboree frogs involved a reduction in the breeding adult population size that would have required an increase in adult mortality, not just failed recruitment to metamorphosis (Hunter 2000). Hence hypotheses implicating factors causing mortality during the post-metamorphic stages are more parsimonious than hypotheses involving only failed recruitment to metamorphosis (Scherer et al 2005). In addition to this, the apparent altitudinal relationship in the observed corroboree frog declines, in combination with the fact that the high-altitude populations are in cooler and moister habitats, is also consistent with the pattern of decline observed in other frog species where B. dendrobatidis has been implicated (Berger et al 1998, McDonald et al 2005.…”
Section: Disease Hypothesis and The Decline Of The Corroboree Frogssupporting
confidence: 74%
“…The initial decline observed for the corroboree frogs involved a reduction in the breeding adult population size that would have required an increase in adult mortality, not just failed recruitment to metamorphosis (Hunter 2000). Hence hypotheses implicating factors causing mortality during the post-metamorphic stages are more parsimonious than hypotheses involving only failed recruitment to metamorphosis (Scherer et al 2005). In addition to this, the apparent altitudinal relationship in the observed corroboree frog declines, in combination with the fact that the high-altitude populations are in cooler and moister habitats, is also consistent with the pattern of decline observed in other frog species where B. dendrobatidis has been implicated (Berger et al 1998, McDonald et al 2005.…”
Section: Disease Hypothesis and The Decline Of The Corroboree Frogssupporting
confidence: 74%
“…One reported cause of these declines is the chytrid fungus, B. dendrobatidis , that is now also present in five European countries, including the UK, and is responsible for amphibian declines in Spain and Switzerland (Garner et al 2005). Scherer et al (2005) also found strong evidence that drastic declines of two populations of boreal toads (Bufo boreas) in the USA were not the result of changes in weather conditions, but were due to B. dendrobatidis. However, the link between outbreaks of B. dendrobatidis and climate change appear to be strong (Pounds et al 2006) and the susceptibility of amphibians to pathogens, such as B. dendrobatidis, is likely to increase under increasing physiological stress, such as that resulting from reduced body condition brought about by changes in climate.…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of a globally disseminated toxin has been presented and the current environmental changes in tropical areas (where most declines have occurred) have occurred previously and have not caused rapid declines (Alexander and Eischeid, 2001). By extrapolating what is known from a few well-studied sites during declines in Australia, Central America, North America, and Spain (Berger et al, 1998;Bosch et al, 2001;Muths et al, 2003;Lips et al, 2006;Schloegel et al, 2006) to sites with similar patterns of decline (Bell et al, 2004;La Marca et al, 2005;Scherer et al, 2005) and using the increasing knowledge of the biology of Bd, we show that chytridiomycosis is the only explanation, for which supporting evidence is available, for these global ''enigmatic'' declines and disappearances of frog populations and species. We also show that the most parsimonious explanation with supporting evidence for the emergence of chytridiomycosis is the introduction and spread of Bd among naive populations of frogs (Laurance et al, 1996;Berger et al, 1999;Daszak et al, 1999;Weldon et al, 2004).…”
Section: Introductionmentioning
confidence: 99%